2007
DOI: 10.1088/0022-3727/40/18/014
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electrical and optical properties of yttrium-doped ZnO thin films prepared by sol–gel method

Abstract: Yttrium-doped ZnO thin films were deposited on silica glass substrates by the sol–gel method. The structural, electrical and optical properties of yttrium-doped ZnO thin films were investigated systematically and in detail. All the thin films have a preferred (0 0 2) orientation. When compared with the electrical resistivity values of films without annealing treatment, the values of films annealed in the reducing atmosphere were decreased by about three orders of magnitude. The lowest electrical resistivity va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…Naturally, both substitutional and interstitial Y dopants were present in the one-pot hydrothermal synthesized ZnO NRs. However, it is the substitutional Y 3+ ions responsible for the expansion of the crystal lattice constant due to the larger ionic radius of Y 3+ (0.92 Å) with respect to Zn 2+ (0.74 Å) [43], an observation consistent with the literature [40,44]. Additional evidence for the substitutional Y 3+ responsible for the expansion of the ZnO lattice constant was demonstrated from the gradual shifting of electron binding energy of Zn 2+ and O 2-as a function of Y doping concentrations [45].…”
Section: Morphology and Structure Characterizationsupporting
confidence: 88%
See 2 more Smart Citations
“…Naturally, both substitutional and interstitial Y dopants were present in the one-pot hydrothermal synthesized ZnO NRs. However, it is the substitutional Y 3+ ions responsible for the expansion of the crystal lattice constant due to the larger ionic radius of Y 3+ (0.92 Å) with respect to Zn 2+ (0.74 Å) [43], an observation consistent with the literature [40,44]. Additional evidence for the substitutional Y 3+ responsible for the expansion of the ZnO lattice constant was demonstrated from the gradual shifting of electron binding energy of Zn 2+ and O 2-as a function of Y doping concentrations [45].…”
Section: Morphology and Structure Characterizationsupporting
confidence: 88%
“…Previous dip coating experiments showed similar effects using YCl 3 [40], hence negatively charged Y 3+ complexes are likely responsible for the shape of the YZO NRs by bonding to the positively charged ZnO (100) plane [41]. Similar behavior has been reported for other X 3+ ions, including Al 3+ , Ga 3+ and In 3+ [41].…”
Section: Morphology and Structure Characterizationsupporting
confidence: 69%
See 1 more Smart Citation
“…5 also it is observed that the UV-NBE emission of the samples is diminished by increasing Cu 2+ ion concentration, indicating that the optical-gap of ZnO semiconductor can be tailored by means of Cu 2+ doping. This last result can be technologically applied in UV radiation sensors fabrication [26].…”
Section: Photoluminescence Studymentioning
confidence: 80%
“…As an intrinsic n-type semiconductor having a hexagonal wurtzite structure with a wide direct band gap of 3.37 eV at room temperature (RT) [12], ZnO could realize a lower resistivity via impurity-doping, such as Group IIIA (e.g., B, Al, Ga and In) [2][3][4]13,14], IVA (e.g., Si, Ge and Sn) [15], IIIB (e.g., Sc and Y) [16,17], and IVB (e.g., Ti and Zr) [18,19] elements. Impurity-doped ZnO thin films have been prepared by various techniques, such as molecular beam epitaxy (MBE) [13], metalorganic chemical vapor deposition (MOCVD) [7], pulsed laser deposition (PLD) [20,21], magnetron sputtering [14,16,18], thermal evaporation [22], spray pyrolysis [23] and sol-gel processing [17]. Among the fabrication techniques, pulsed laser deposition provides several advantages for growing high-performance TCO films [20,21].…”
Section: Introductionmentioning
confidence: 99%